2.4*0-2.6y=-7.5

Simple and best practice solution for 2.4*0-2.6y=-7.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.4*0-2.6y=-7.5 equation:


Simplifying
2.4 * 0 + -2.6y = -7.5

Multiply 2.4 * 0
0.0 + -2.6y = -7.5

Anything times zero is zero.
0.0 + -2.6y = -7.5
Remove the zero:
-2.6y = -7.5

Solving
-2.6y = -7.5

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-2.6'.
y = 2.884615385

Simplifying
y = 2.884615385

See similar equations:

| -3.6(-1.5-2.3x)=15.202+4.9x | | 3x+7=89 | | 4p+1-p= | | x*-x=30 | | 3x+7-7x*12x=4x+9 | | 25w^4-40w^2+u-16u^2=0 | | -6x^2+19x-10=0 | | 3+3/18(18/3) | | -9=8x-9/9 | | 16=9-h | | 3y-5=y+13 | | 22+-2x=20 | | 2x+4y=33 | | -69.716=-2.9(5.8+3.2v) | | 7/3(6x-3)=6/7(14x-21) | | 10y^3-55y^2-105y=0 | | 4n^2+7n= | | (m+14)/4=6 | | 16q^2=25 | | (2x-2)(2x+2)= | | 3-4m-5m=21 | | (7x-3)(2x+1)= | | 3t^3-7t^2-3t+7=0 | | 106=2x+(-5x-5) | | 4x+1=10x-8 | | 2m+2m=-16 | | -17*0+13y=48 | | 12n+3=n+10 | | 3r^3-192r=0 | | 8d-12=10d+4 | | -2=r-6-1 | | 4y+4=4x |

Equations solver categories